Deuterium retention in tungsten irradiated by different ions. (21st July 2020) - Wielunska, B.; Mayer, M.; Schwarz-Selinger, T.; Sand, A.E.; Jacob, W.
Abstract: Tungsten was irradiated with different ion species (H, D, He, Si, Fe, Cu, W) at energies between 0.3 and 20.3 MeV to two different calculated damage levels of 0.04 dpa and 0.5 dpa. Samples were exposed to a low-temperature deuterium (D) plasma at 370 K to decorate the radiation defects. D retention was studied by nuclear reaction analysis using the D( 3 He, p) α reaction and by thermal desorption spectroscopy. For tungsten irradiated by light ions (H, D, He) the depth profiles as well as D desorption spectra show clear differences. On the other hand, tungsten irradiated by medium- to high-mass ions (Si, Cu, Fe, W) to identical dpa values shows similar D depth profiles and nearly identical D desorption spectra, i.e. the D retention is comparable. Since the large differences in the primary recoil energy distribution due to different incident energies of the different ions (Si, Cu, Fe, W) do not result in a different D retention, we assume that neutron irradiation of tungsten in a future fusion reactor will result in a similar D retention as in tungsten damaged by medium- to high-mass ions. Irradiation with ions with a mass of 28 amu (Si) or higher seems to be a suitable proxy for investigating the influence of displacement damage by neutrons on D retention.